Calcifying cystic odontogenic tumor of maxila: A case report - Assunçao-Júnior, José Narciso Rosa; Oliveira, Letícia Almeida; Cadavid, Ana Maria Hoyos; Lemos-Júnior, Celso Augusto; Teixeira, Victor Perez (Journal of Oral Diagnosis, 2017)
The calcifying cystic odontogenic tumor (CCOT) is an uncommon pathology, representing about 2% of all odontogenic cysts and tumors. Generally, is presented as slow growth, asymptomatic, without predilection of gender or location. The most common radiographic presentation is radiolucent image with radiopaque areas, especially in the lesion periphery, unilocular, expansive and well- defined margin. The purpose of this report is to describe the case of a 16-year-old boy with a painless and progressive increase of volume on the face, which started 7 months ago. In oroscopy, we observed an expansive increase of volume in right maxilla, extending from premolars to molars on the same side. In computed tomography, it was possible to observe an unilocular, expansive image in right maxilla. After incisional biopsy, the histopathological analysis evidenced epithelial neoplasia of odontogenic origin that presents cystic portions and solid portions. In the cystic portions, there is an epithelial lining which basal cells are cuboidal or cylindrical arrangement in palisade, presence of ghost cells and dystrophic mineralization, confirming the diagnosis of calcifying cystic odontogenic tumor. Excision and curettage were performed under general anesthesia. The excised tumor was analyzed, confirming the diagnosis of CCOT and the patient has been in clinical and radiographic follow- up for a period of 5 years, without signs of relapses.